Analisis Strategi Pemasaran (Marketing Mix) Pada Makanan Tradisional Tiwul Kukus Untuk Meningkatkan Penjualan - Adestya Nindi Salsa; Serly Faisa Nur Fatika Sari; Berli Ananta; Dika Prawita (PT Pustaka Cendekia Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) engaged in the processing of Traditional Steamed Tiwul Food still face challenges in marketing their processed products. This study aims to analyze the marketing strategies of Traditional Steamed Tiwul Food products in Gunungkidul. The method used in this study is a quantitative method through observation, interviews, and documentation, which are then presented in the form of data. The analysis used is an analysis of the influence of the Marketing Mix (product, price, promotion, and location) on the marketing performance of Micro, Small, and Medium Enterprises producing Tiwul Kukus in Gunungkidul. The research results indicate that the marketing strategies for Tiwul Kukus products in Gunungkidul still face several challenges, particularly in the areas of promotion and distribution. The Marketing Mix analysis indicates that the product and price elements have been implemented and executed effectively, but promotion and location still need to be improved to support the marketing performance of the Tiwul Kukus MSME. Data from observation, interviews, and documentation suggest that the use of digital media and the selection of appropriate sales locations play a crucial role in enhancing the product's competitiveness.